2017
DOI: 10.21270/archi.v6i8.2214
|View full text |Cite
|
Sign up to set email alerts
|

Influence of particulate matter and meteorological conditions on multiple sclerosis relapse: a preliminary study in São Paulo, Brazil

Abstract: Introduction: Multiple sclerosis (MS) is a chronic, inflammatory, and demyelinating disease of the central nervous system, which in some cases may be characterized by recurrent relapses of inflammation that cause mild to severe neurological disability. Some studies around the world have associated the increase of systemic inflammatory responses and neuro-inflammation of patients with exposure to high levels of particulate matter (PM 10 ) and certain conditions of temperature and humidity. Materials and methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…In Italy, a study found significant relationships in the occurrence of MS relapses due to exposure to PM 10 [14]. A similar study was carried out in São Paulo city, Brazil, in which significant relationships were also found between MS relapses and PM 10 [5]. In addition to PM 10 , other pollutants may be related to MS relapses, such as sulfur dioxide (SO 2 ), nitrogen oxides (NO x ), and nitrogen dioxide (NO 2 ) [6,9,13].…”
Section: Introductionmentioning
confidence: 71%
See 3 more Smart Citations
“…In Italy, a study found significant relationships in the occurrence of MS relapses due to exposure to PM 10 [14]. A similar study was carried out in São Paulo city, Brazil, in which significant relationships were also found between MS relapses and PM 10 [5]. In addition to PM 10 , other pollutants may be related to MS relapses, such as sulfur dioxide (SO 2 ), nitrogen oxides (NO x ), and nitrogen dioxide (NO 2 ) [6,9,13].…”
Section: Introductionmentioning
confidence: 71%
“…A study in Italy showed that high concentrations of PM 10 are a risk factor of up to 46% for the occurrence of MS relapses [14]. Diniz et al [5] showed that there is a significant correlation between PM 10 and MS relapses in São Paulo city. PM 10 concentrations in São Paulo city frequently surpass the WHO standard levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding is consistent with some of the studies and inconsistent with others. For examples, a Brazilian study found a positive correlation between RH and male MS admissions (r = 0.29, p < 0.01), while the correlation in females was insignificant (r = 0.04, p > 0.05) [23]. Further confusing the literature, an Iranian [17] and an Italian [24] study reported insignificant relationships between RH and MS.…”
Section: Discussionmentioning
confidence: 99%